Active Electron Density Modulation of Co3O4‐Based Catalysts Enhances their Oxygen Evolution Performance. Issue 17 (19th March 2020) - He, Dong; Song, Xianyin; Li, Wenqing; Tang, Chongyang; Liu, Jiangchao; Ke, Zunjian; Jiang, Changzhong; Xiao, Xiangheng
Abstract: Despite the fact that many strategies have been developed to improve the efficiency of the oxygen evolution reaction (OER), the precise modulation of the surface electronic properties of catalysts to improve their catalytic activity is still challenging. Herein, we demonstrate that the surface active electron density of Co3 O4 can be effectively regulated by an argon‐ion irradiation method. X‐ray photoelectron and synchrotron x‐ray absorption spectroscopy, UV photoelectron spectrometry, and DFT calculations show that the surface active electron density band center of Co3 O4 has been upshifted, leading to a significantly enhanced absorption capability of the oxo group. The optimized Co3 O4 ‐based catalysts exhibit an excellent overpotential of 260 mV at 10 mA cm −2 and Tafel slope of 54 mV dec −1, superior to the capability of the benchmark RuO2, representing one of the best Co‐based OER catalysts. This approach could guide the future rational design and discovery of ideal electrocatalysts. Abstract : Surface enhancement : The surface electronic structure of Co3 O4 can be effectively regulated, thereby leading to substantial enhancement of its oxygen evolution reaction performance.